Respuesta :

___________________________________

[tex]\huge\underline{\tt{\red{Problem:}}}[/tex]

[tex]\quad\quad\quad\quad\tt{f(x) = 4x + 1} \: and \: g(x) = {x}^{2} - 5[/tex]

[tex]\huge\underline{\tt{\red{Fomula:}}}[/tex]

[tex]\quad\quad\quad\quad\huge\tt{( \: f \: • \: g \: )}[/tex]

[tex]\huge\underline{\tt{\red{Solution:}}}[/tex]

[tex]\quad\quad\quad\quad\tt{(f \:•\: g)(x) = (4x + 1} \: ) ( {x}^{2} - 5)[/tex]

Step by step first:

[tex]\quad\tt{ ⟶ { 4x \times {x}^{2} = \boxed{4 {x}^{3}}} }[/tex]

[tex] \quad\tt{ ⟶ { 1 \times {x}^{2} = \boxed{{x}^{2}}} }[/tex]

[tex] \quad\tt{ ⟶ { 4x \times ( - 5) = \boxed{ - 20x}} }[/tex]

[tex]\quad\tt{ ⟶ { 1 \times ( - 5) = \boxed{ - 5}} }[/tex]

It will look like this:

[tex]\quad\quad\quad\quad\tt{(f \:•\: g)(x) = (4 {x}^{3} + {x}^{2} - 20x - 5 )}[/tex]

[tex]\huge\underline{\tt{\red{Answer:}}}[/tex]

[tex]\quad\quad \underline{ \boxed{\tt{ \red{(f \:•\: g)(x) = 4 {x}^{3} + {x}^{2} - 20x - 5 }}}}[/tex]

___________________________________

#CarryOnLearning

✍︎ C.Rose❀

Ver imagen Аноним
ACCESS MORE